Exploring the therapeutic mechanisms of Yikang decoction in polycystic ovary syndrome: an integration of GEO datasets, network pharmacology, and molecular dynamics simulations - Miao, Jiang; Gao, LiXuan; Liu, Xi; Cai, Wenpin; Chen, Lei; Chen, Mojinzi; Sun, Yun (Frontiers in Medicine, 2024)
Objective: The incidence of Polycystic Ovary Syndrome (PCOS) is increasing annually. This study aims to investigate the therapeutic mechanisms of Yikang Decoction (YKD) in the treatment of PCOS through the integration of GEO datasets, network pharmacology, and dynamic simulation. Methods: Active ingredients of YKD and their targets were collected from the Traditional Chinese Medicine Systems Pharmacology (TCMSP) platform. Disease-relevant targets for PCOS were retrieved from several databases, including GeneCards, OMIM, PharmGKB, DrugBank, and GEO. The underlying pathways associated with the overlapping targets between YKD and PCOS were identified using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. The mechanisms of interaction between the core targets and components were further explored through molecular docking and molecular dynamics (MD) simulations. Results: 139 potential active components and 315 targets of YKD were identified. A topological analysis of the PPI network revealed 10 core targets. These targets primarily participated in the regulation of biological processes, including cell metabolism, apoptosis, and cell proliferation. The pathways associated with treating PCOS encompassed PI3K-Akt signaling pathway, Lipid and atherosclerosis, MAPK signaling pathways, and Endocrine resistance signaling pathways. Moreover, molecular docking and molecular dynamics simulation have been shown to reveal a good binding capacity between active compounds and screening targets.This study systematically investigates the multi-target mechanisms of YKD in the treatment of PCOS, with preliminary verification provided through molecular docking and molecular dynamics simulations. The findings offer compelling evidence supporting the efficacy of YKD in treating PCOS.